Global burden and trends of childhood non-Hodgkin lymphoma from 1990 to 2021 - Xie, Jing; Xu, Jian-She; Huang, Jiang-Wei; Zheng, Yi-Shan (Frontiers in Pediatrics, 2025)
BackgroundChildhood non-Hodgkin lymphoma (NHL) is a significant contributor to pediatric cancer morbidity and mortality worldwide. This study aims to assess the global, regional, and national burden of childhood NHL from 1990 to 2021, using data from the Global Burden of Disease (GBD) 2021 study.MethodsIncidence, mortality, and disability-adjusted life years (DALYs) related to childhood NHL were analyzed across 204 countries and 21 geographic regions using standardized methods from the GBD 2021 study. Estimated annual percentage change (EAPC) and average annual percentage change (AAPC) were calculated to evaluate long-term trends. Frontier and inequality analyses were applied to assess the relationship between sociodemographic development and disease burden.ResultsIn 2021, there were 20,788.76 (95% uncertainty intervals, UI: 17,199.49–25,305.83) new childhood NHL cases globally, with an incidence rate of 1.03 per 100,000 (95% UI: 0.85–1.26). The global mortality rate decreased from 0.75 (95% UI: 0.57–0.89) in 1990 to 0.45 (95% UI: 0.36–0.56) in 2021 (EAPC: −1.49, 95% confidence interval, CI: −1.60 to −1.39). DALYs rates also declined from 63.38 (95% UI: 48.09–75.72) in 1990 to 37.83 (95% UI: 29.95–47.17) in 2021 (EAPC: −1.51, 95% CI: −1.61 to −1.40). Burden reductions were most significant in high-SDI regions. In contrast, several low- and middle-SDI regions, particularly in Sub-Saharan Africa, experienced either slow declines or rising burden, with Southern Sub-Saharan Africa showing the largest increase in DALYs rate.ConclusionsWhile advancements in treatment and healthcare infrastructure have contributed to declining childhood NHL mortality, persistent disparities highlight the need for targeted interventions in low-SDI regions. Strengthening pediatric oncology capacity, expanding treatment accessibility, and enhancing early detection efforts are crucial for reducing global inequalities in childhood NHL outcomes.